EXAMINING THE INTERPLAY OF TALENT AND KNOWLEDGE MANAGEMENT IN SHAPING EMPLOYEE PERFORMANCE: A STUDY ON SURABAYA INTERNATIONAL AIRPORT - Muhammad Rifqi Ramadhan; Kustini Kustini (CV. Radja Publika, 2023)
Managing talented employees is important to encourage companies to compete domestically and internationally. Likewise, knowledge can increase employees to be more productive so as to achieve maximum performance. The purpose of this research is to determine the impact of Talent Management and Knowledge Management on the performance of employees of PT Angkasa Pura I Juanda Surabaya, which is engaged in airports. This research uses a quantitative approach that applies questionnaires and interviews as data collection techniques. The population studied amounted to 52 supervisors and the sampling method used a saturation sampling approach. The analysis technique applied in this research is Partial Least Square (PLS). The results in this research indicate that Talent Management and Knowledge Management contribute positively to the performance of employees of PT Angkasa Pura I Juanda Surabaya.